2007
DOI: 10.1172/jci32285
|View full text |Cite
|
Sign up to set email alerts
|

IL-1R1/MyD88 signaling and the inflammasome are essential in pulmonary inflammation and fibrosis in mice

Abstract: The molecular mechanisms of acute lung injury resulting in inflammation and fibrosis are not well established. Here we investigate the roles of the IL-1 receptor 1 (IL-1R1) and the common adaptor for Toll/IL-1R signal transduction, MyD88, in this process using a murine model of acute pulmonary injury. Bleomycin insult results in expression of neutrophil and lymphocyte chemotactic factors, chronic inflammation, remodeling, and fibrosis. We demonstrate that these end points were attenuated in the lungs of IL-1R1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
416
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(435 citation statements)
references
References 84 publications
(91 reference statements)
16
416
2
1
Order By: Relevance
“…Mice lacking the IL-1R1 receptor showed significantly reduced cellular infiltrates, alveolar wall destruction and collagen deposition. Moreover, blockade of the IL-1R1 receptor by exogenous IL-Ra (anakinra) dramatically reduced neutrophil influx and the formation of bleomycin-induced fibrosis in mice [8]. Altogether, IL-1 seems to be a critical cytokine and may possibly be a therapeutic target in IPF.…”
Section: Il-1 Receptor Antagonist In Ipfmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice lacking the IL-1R1 receptor showed significantly reduced cellular infiltrates, alveolar wall destruction and collagen deposition. Moreover, blockade of the IL-1R1 receptor by exogenous IL-Ra (anakinra) dramatically reduced neutrophil influx and the formation of bleomycin-induced fibrosis in mice [8]. Altogether, IL-1 seems to be a critical cytokine and may possibly be a therapeutic target in IPF.…”
Section: Il-1 Receptor Antagonist In Ipfmentioning
confidence: 99%
“…Mice with bleomycin-induced fibrosis have an up-regulated expression of IL-1b mRNA after instillation of bleomycin [20], and addition of recombinant IL-1b induces fibrotic remodelling [8]. Overexpression of IL-1b in rat lungs after intratracheal administration of bleomycin was associated with severe progressive tissue fibrosis in the lung, characterized by the presence of myofibroblasts, fibroblast foci and significant extracellular accumulations of collagen and fibronectin [4].…”
Section: Il-1 Receptor Antagonist In Ipfmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Myofibroblasts extensively produce and secrete ECM proteins, 9 and are involved in abnormal wound repair and remodeling through various mechanisms, including deregulation of the balance between matrix metallopeptidases (MMPs) and tissue inhibitors of MMPs (TIMPs). 10 It was previously believed that the origin of myofibroblasts is solely peribronchiolar and perivascular fibroblasts that transdifferentiate to myofibroblasts in response to various stimuli, in particular TGF-b 1 . 11 However, recently, it was shown that lung epithelial cells undergo epithelial-mesenchymal transition (EMT) to become myofibroblasts after treatment with TGF-b 1 in vitro.…”
mentioning
confidence: 99%
“…Lung fibrosis induced by bleomycin delivered to animals via different routes has different pattern of foci distributions. Using the bleomycin-induced pulmonary fibrosis model, it has been previously reported that pulmonary inflammation and fibrosis are mediated by secretion of the proinflammatory and pro-fibrotic cytokine IL-1β through Nlrp3 inflammasome activation and IL-1R1/MyD88 signaling (Chen et al, 2015;Francois et al, 2015;Gasse et al, 2007). Fibrosis associated with bleomycin treatment has also been linked to toxic reactive oxygen and nitrogen species produced by infiltrating inflammatory cells (Yamazaki et al, 1998).…”
Section: Introductionmentioning
confidence: 99%